2015
DOI: 10.1186/s40781-014-0037-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of by-product feed-based silage on feeding, rumination, and excretion in growing Hanwoo heifers

Abstract: This study investigated the effects of feeding by-product feed (BF)-based silage on the behavior of growing Hanwoo heifers. Twelve Hanwoo heifers (13.2 months-old, 315 kg body weight; four heifers per pen) were assigned to three diets: a rice straw (RS) diet (concentrate mix and free access to RS), a RS and BF-based silage (RSBFS) diet (concentrate mix and free access to RS and BF-based silage), and a BF-based silage (BFS) diet (concentrate mix and free access to BF-based silage). Behavior was recorded for 5 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…In this context, we started a project to use SMS as roughage for cattle. It has been reported that the silage containing SMS can be used as a roughage for ruminants [3]- [5], although some adverse effects, such as reduced rumination and chewing activity, were observed [6], which may be because of the shorter fiber length of SMS used in this study: it is well known that there is a positive relationship between fiber length and ruminating time or total chewing time [7], [8]. If this assumption holds true, the above problem may be solved when materials having longer fiber length are used as base materials.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, we started a project to use SMS as roughage for cattle. It has been reported that the silage containing SMS can be used as a roughage for ruminants [3]- [5], although some adverse effects, such as reduced rumination and chewing activity, were observed [6], which may be because of the shorter fiber length of SMS used in this study: it is well known that there is a positive relationship between fiber length and ruminating time or total chewing time [7], [8]. If this assumption holds true, the above problem may be solved when materials having longer fiber length are used as base materials.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that SMS-MP can be used as ruminant feed without any deleterious effects on cattle eating behavior. Similarly, the current study found no effect of SMS-MP on feed intake and apparent digestibility of OM, EE, and CP in sika doe [ 20 ]. However, the SMS-MP reduced the digestibility of DM, which needs further study.…”
Section: Discussionmentioning
confidence: 53%
“…Microbial fermentation inside the silo produces an array of end products and may exchange many nutritive factors of a forage (Kung Jr et al, 2018). Feed in the form of by-product feed-based-silage (BF-silage) given to steers produces fiber-rich feed for growth or fattening and increases the intake of DM and neutral detergent fiber (NDF) (Kim et al, 2015a(Kim et al, , 2013(Kim et al, , 2015b; by-product feed-based-silage (BF-silage) results in higher energy and protein utilization values, and lower fiber digestion in sheep (Seok et al, 2016) and reduce the use of feed supplements (Hendricks et al, 2021).…”
Section: Introductionmentioning
confidence: 99%